Formulation and testing of a water-borne primer containing chestnut tannin - Pardini, Oscar Ricardo (1998)
In this work an aqueous primer containing chestnut tannin and phosphoric acid was developed and its anticorrosive properties assessed by different conventional tests. Treated Steel ponéis coated with an anticorrosive paint and a topcoat were subjected to the salí spray test, humidity chamber, mechanical tests (adhesión and flexibility) and electrochemical tests (corrosión potential, ionic resistance and polarization resistance). Electrochemical tests were done employing only ponéis primed with the primer. The binder employed in this research was prepared in the laboratory by emulsión polymerization of acrylic monomers. It was found that the tested formulation protected Steel against corrosión incorporating corrosión producís to the film as ferric tannates and avoiding oxide formation. Undercutting rusting was not significant and the scratch line stood free from oxides. The good stability of the binder in low pH media and the interaction of the binder with the substrate are decisive factors in the performance of this aqueous pretreatment system.